A multicenter, randomized, double-blind study comparing different FK778 doses (manitimus) with tacrolimus and steroids vs. MMF with tacrolimus and steroids in renal transplantation - Włodarczyk, Zbigniew; Krämer, Bernhard (BMC nephrology, 2012)
This multicenter phase II study in renal transplantation compared 3 concentration-controlled ranges of FK778 (manitimus) with mycophenolate mofetil (MMF) both given in combination with tacrolimus and corticosteroids.